2014
DOI: 10.1080/0966369x.2013.879103
|View full text |Cite
|
Sign up to set email alerts
|

Gender equality: a core dimension in Rural Development Programmes in Austria?

Abstract: The supranational gender equality regime of the European Union (EU), in place since the 1990s, affects gender-related social policy including the so-called 'gender-neutral' policy fields such as the common agricultural policy and rural development policy. Especially, the implementation of gender equality in all policy fields through the strategy of gender mainstreaming in EU Structural Funds and Rural Development Programmes has become a key challenge for political and administrative players and stakeholders. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…It is found that education and gender equality are vital factors for individual empowerment for rural people. These findings were consistent with previous studies conducted by Jayesh and Peravurani [68] and Oedl-Wieser [69]. [70], BuchoriPramitasari [71], and Ahmad and Talib [58].…”
Section: Discussionsupporting
confidence: 93%
“…It is found that education and gender equality are vital factors for individual empowerment for rural people. These findings were consistent with previous studies conducted by Jayesh and Peravurani [68] and Oedl-Wieser [69]. [70], BuchoriPramitasari [71], and Ahmad and Talib [58].…”
Section: Discussionsupporting
confidence: 93%
“…While gender mainstreaming has been adopted by most countries since 1995 as an overarching policy in various sectors, scholars show that action on the ground is far from robust and mecha-nisms have been wanting (Oedl-Wieser, 2015;Moser and Moser, 2005;Parpart, 2014;Walby, 2005).Authors write about the lack of institutional backup (Piálek, 2008).While some point out the near impossibility of working seriously with mainstreaming in a patriarchal system (Prügl, 2010), others (George, 2007; show how gender mainstreaming needs to be responsive to the culturally specific contexts to capture the complex realities in which gender policies are implemented.…”
Section: The Gap Between Policy and Practicementioning
confidence: 99%
“…This has implications for access to benefits, capital for investment, and training and professional advice. Women are very underrepresented in lifelong agricultural training programmes and in farming unions (Shortall, 1999;Prugl, 2010a;Cernic-Istenic 2013;Oedl-Wieser 2013). The fact that the public domain of farming is almost entirely male takes on a cultural power of its own, making it even more difficult for women to participate (Shortall, 2010).…”
Section: Gendered Inequalities In European Agriculturementioning
confidence: 99%
“…There is evidence to suggest that the RDP is adopted in ways that reflect existing gender imbalances, and that gender mainstreaming is not considered in how programmes are implemented. In other words, gender mainstreaming is sometimes circumvented by cultural norms and established patterns of practice (Oedl-Wieser 2013;Cernic-Istenic 2013, Prugl, 2010. Where there have been attempts to address gender mainstreaming issues, either through projects across Europe or feminist research calling for change, they have in general tended to focus on the symptoms of gender inequality in agriculture, rather than addressing the cause.…”
Section: Member States and The Commission Shall Promote Equality Between Men And Women…this Includes The Stages Of Design Implementation mentioning
confidence: 99%